2021
DOI: 10.1016/j.apcatb.2021.119907
|View full text |Cite
|
Sign up to set email alerts
|

Design of an intercalated Nano-MoS2 hydrophobic catalyst with high rim sites to improve the hydrogenation selectivity in hydrodesulfurization reaction

Abstract: The preparation of the intercalated lamellar hydrophobic nano-MoS 2 (size: 60-100 nm, interlayer spacing: 0.7-1.2 nm) through the substitution of organic amine for inorganic ammonium salt and the subsequent catalytic reaction as a hydrodesulfurization catalyst is presented. The intercalated amine groups broadened the interspacing of the lamellar nano-MoS 2 and promoted the formation of hydrophobic stacking structure consisting of stable monolayers. The high hydrophobicity of the nano-MoS 2 monolayer catalyst w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…The HDS of the model reactant (4,6-DMDBT) is assumed to be the pseudo-first-order reaction, and the rate constant k HDS (mol g –1 h –1 ) was determined by the following equation , where W refers to the molar weight of the reactant (mol), m is the catalyst weight (g), t is the reaction duration (s), and Δ C is the conversion of reactant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HDS of the model reactant (4,6-DMDBT) is assumed to be the pseudo-first-order reaction, and the rate constant k HDS (mol g –1 h –1 ) was determined by the following equation , where W refers to the molar weight of the reactant (mol), m is the catalyst weight (g), t is the reaction duration (s), and Δ C is the conversion of reactant.…”
Section: Methodsmentioning
confidence: 99%
“…The production of sulfur-free fuel oil from petroleum materials, especially from low-grade diesel, has been a pressing mission because of increasingly stringent standards on the maximum sulfur content of diesel fuel. However, the production of ultraclean diesel is limited by the refractory sulfur compound 4,6-di­methyl­di­benzo­thio­phene (4,6-DMDBT) with alkyl groups at the 4 and 6 positions that resulted in the space-shield effect. , Industrially, hydrodesulfurization (HDS) is the most effective and widely used desulfurization technology to reduce the sulfur concentration of fuel oil to below 10 ppm. Co­(Ni)­MoS supported over Al 2 O 3 is a commonly used HDS catalysts in the petroleum refining industry.…”
Section: Introductionmentioning
confidence: 99%
“…In general, there are two reaction pathways for DBT in the HDS process: 30,31 one is the direct desulfurization pathway (DDS) to generate biphenyl (BP); another is the hydrodesulfurization pathway (HYD) which produces cyclohexylbenzene (CHB) and dicyclohexane (BCH) (Chart 1). According to analyzing the content ratio of BP and (CHB + BCH) in the product, the selectivity of the two HDS pathways can be obtained.…”
Section: Hds Catalytic Performance Evaluationmentioning
confidence: 99%
“…Wang et al reported oxygen-intercalated MoS 2 with obviously expanded interlayer spacing for catalytic transfer hydrogenation of nitroarenes, [19,37] but the intercalated structure was unfortunately ignored. Liu et al [38] claimed intercalated lamellar hydrophobic nano-MoS 2 as a hydrodesulfurization catalyst, in which the structure-activity relationship has not been sufficiently understood due to the absence of effective control on interlayer chemistry and lattice defects.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al. [ 38 ] claimed intercalated lamellar hydrophobic nano‐MoS 2 as a hydrodesulfurization catalyst, in which the structure‐activity relationship has not been sufficiently understood due to the absence of effective control on interlayer chemistry and lattice defects.…”
Section: Introductionmentioning
confidence: 99%